2011
DOI: 10.1161/circheartfailure.110.959957
|View full text |Cite|
|
Sign up to set email alerts
|

Thromboembolism and Antithrombotic Therapy in Patients With Heart Failure in Sinus Rhythm

Abstract: H eart failure (HF) represents a major and growing public health problem because of its prevalence, incidence, morbidity, mortality, and economic costs. The prevalence of HF is 2% to 3% of the general population. 1 Five million Americans are affected, with Ͼ550 000 cases diagnosed each year. 2 The mortality rate from severe HF remains Ͼ60% within 5 years of diagnosis, and 50% of hospitalized patients with HF require readmission within 6 months of discharge. In the US estimated costs amount to Ͼ $35 billion per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 44 publications
0
15
0
2
Order By: Relevance
“…In contrast, conflicting data have been observed with regard to the association of platelet biomarkers with prognosis. 7,9,21,23,24 Notably, the small size of these previous studies underscores the need for ongoing exploration of the biology of platelet activation in HF. n/a n/a n/a n/a Kandis et al 10 Acute vs chronic HF Acute>chronic HF Yes n/a n/a n/a n/a n/a n/a n/a No differences between groups; decrease at followup for acute HF n/a n/a n/a n/a …”
Section: Evidence Of Platelet Activation In Hfmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, conflicting data have been observed with regard to the association of platelet biomarkers with prognosis. 7,9,21,23,24 Notably, the small size of these previous studies underscores the need for ongoing exploration of the biology of platelet activation in HF. n/a n/a n/a n/a Kandis et al 10 Acute vs chronic HF Acute>chronic HF Yes n/a n/a n/a n/a n/a n/a n/a No differences between groups; decrease at followup for acute HF n/a n/a n/a n/a …”
Section: Evidence Of Platelet Activation In Hfmentioning
confidence: 99%
“…Several mechanisms that are activated in chronic HF and further enhanced during acute decompensation may promote a prothrombotic state 9 and may explain, in part, the observed increased platelet reactivity. 5 Endothelial damage and dysfunction along with imbalances in nitric oxide production and increased expression of adhesion molecules may lead to enhanced platelet adhesion and activation.…”
Section: Pathophysiology Of Platelet Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Disappointment continued with publication of the randomized controlled ASCEND-HF (Acute Study of Clinical Effectiveness of Nesiritide in Decompensated Heart Failure). In this study of 7,000 patients, nesiritide was not associated with a change in the rate of rehospitalization or State-of-the-Art Reviews Table 2 State-of-the-Art Reviews "Cirrhotic Cardiomyopathy" (10) "Update 2011: Clinical and Genetic Issues in Familial Dilated Cardiomyopathy" (11) "Exercise Training in Heart Failure: Practical Guidance" (12) "The Role of Exercise Training in Heart Failure" (13) "Heart Failure and Chronic Obstructive Pulmonary Disease" (14) "Heart Failure With Preserved Ejection Fraction: Pathophysiology, Diagnosis, and Treatment" (15) "Medical and Surgical Treatment of Acute Right Ventricular Failure" (16) "Obstructive Sleep Apnea and Heart Failure" (17) "Pregnancy in Patients With Pre-Existing Cardiomyopathies" (18) "Thromboembolism and Antithrombotic Therapy in Patients With Heart Failure in Sinus Rhythm: Current Status and Future Directions" (19) "Troponin Elevation in Heart Failure" (20) death and had a nonsignificant effect on dyspnea (21). Moreover, the DOSE (Diuretic Optimization Strategies Evaluation) trial showed no significant difference in symptoms or renal function when loop diuretic therapy was administered by continuous infusion or bolus and no significant difference in outcomes at low versus high dose (23).…”
Section: Management Of Hfmentioning
confidence: 99%
“…Sin embargo, en la evaluació n inicial deberían utilizarse siempre las escalas CHA 2 DS 2 -VASc y HAS-BLED para establecer la relació n riesgo-beneficio entre iniciar y no iniciar el tratamiento con ACO 15 . En la prá ctica clínica, sin embargo, los ACO se administran con mayor asiduidad: entre el 10 y el 30% de los pacientes con IC sin FA reciben este tratamiento 16 . En la prá ctica clínica, sin embargo, los ACO se administran con mayor asiduidad: entre el 10 y el 30% de los pacientes con IC sin FA reciben este tratamiento 16 .…”
unclassified